2014
DOI: 10.1093/nar/gkt1416
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosome MKT1 and the RNA-binding protein ZC3H11: interactions and potential roles in post-transcriptional regulatory networks

Abstract: The trypanosome zinc finger protein ZC3H11 binds to AU-rich elements in mRNAs. It is essential for survival of the mammalian-infective bloodstream form, where it stabilizes several mRNAs including some encoding chaperones, and is also required for stabilization of chaperone mRNAs during the heat-shock response in the vector-infective procyclic form. When ZC3H11 was artificially ‘tethered’ to a reporter mRNA in bloodstream forms it increased reporter expression. We here show that ZC3H11 interacts with trypanoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
151
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(157 citation statements)
references
References 86 publications
5
151
1
Order By: Relevance
“…Intriguingly, the same phenomenon was seen in cells in which deadenylation pathways (CAF1, CNOT10, PAN2), or the exosome (RRP45), were depleted, and also after RNAi targeting both MKT1 and CTR9. MKT1 and CTR9 do not have the same function as PUF2-indeed, MKT1 increased mRNA levels in a tethering assay (37), the opposite effect to that of PUF2. One possibility is that the length-related effects of PUF2 depletion are indirect, through reductions in mRNAs encoding degradation machinery components.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Intriguingly, the same phenomenon was seen in cells in which deadenylation pathways (CAF1, CNOT10, PAN2), or the exosome (RRP45), were depleted, and also after RNAi targeting both MKT1 and CTR9. MKT1 and CTR9 do not have the same function as PUF2-indeed, MKT1 increased mRNA levels in a tethering assay (37), the opposite effect to that of PUF2. One possibility is that the length-related effects of PUF2 depletion are indirect, through reductions in mRNAs encoding degradation machinery components.…”
Section: Discussionmentioning
confidence: 88%
“…We wondered whether protein coding region length would always influence expression in cells experiencing growth inhibition, so we compared our results with RNASeq or microarray data from other cell lines with RNAi that targeted expression of essential proteins (see Table S4, sheet 4, in the supplemental material). MKT1 is partially associated with polysomes and may be required for translation (37). We were startled to find that there was a correlation between the effects of RNAi targeting PUF2 and those for MKT1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the entire region downstream of residue 185 was required for activity [19]. This portion contains, at residues 196–199, a four-residue motif (HNPY) that is required for interaction with the post-transcriptional regulator MKT1, and beyond that an additional region that interacts with the PABP-interacting protein PBP1 [19].…”
Section: Resultsmentioning
confidence: 95%
“…Development of an improved MS2 coat protein tethering system for identifying trans-acting factors regulating SIDER2 retroposon-mediated mRNA decay in Leishmania So far, the λN peptide has been used successfully to tether RBPs to a particular RNA of interest in the related Trypanosoma species (Delhi et al 2011;Wurst et al 2012;Droll et al 2013;Jha et al 2014;Singh et al 2014). Here, we have developed an improved MS2 coat protein tethering system adapted for use in Leishmania to attach RNA-binding proteins (RBPs) specifically to a reporter RNA.…”
Section: Resultsmentioning
confidence: 99%